Viable cell sorting by fluidized bed centrifugation enables novel cultivation strategies - Saballus, Martin; Reger, Lucas Nik; Obser, Robin; Niemann, Julia; Wijffels, Rene H.; Martens, Dirk E.; Kampmann, Markus (Frontiers in Bioengineering and Biotechnology, 2025)
In biopharmaceutical manufacturing, continuous perfusion cultivation enables high space-time yields and increased plant utilization, which are critical targets for modern upstream process intensification. However, filter-based cell retention devices, utilized in these processes, have significant disadvantages: Significant sieving effects and the risk of filter blockage alongside the retention of harmful substances and non-viable cells, represent a major challenge and often reduce the viability of the culture. To enable the next-generation of continuous processes, novel cell retention strategies are required. Therefore, the aim of this study was to develop an approach for large-scale sorting of viable and non-viable cells and to investigate its applicability for novel continuous cultivation strategies. To remove non-viable cells and thus to enrich viable cells in the culture, a single-use fluidized bed centrifuge (FBC) was used, which is usually applied for concentration and washing of mammalian cells. A novel FBC method was introduced by overloading the centrifuge chambers that allows high throughput sorting depending on the culture´s viability. The impact of the sorting on the subsequent cultivation and productivity of the cells was investigated in a multi-parallel 15 mL bioreactor setup. Cell sorting after regular fed-batch cultivation showed +14% increase of viability, continued cell growth, and thus +13% higher titers. Thereafter, periodic cell sorting was tested on a 5-L scale bioreactor, combining the advantageous characteristics of fed-batch and perfusion cultivation. The feasibility was successfully demonstrated for 20 days, achieving a high average space-time yield of 0.75 g/L/d. In both cultivation trials, up to +38% higher cell specific antibody productivities were found after cell sorting. Overall, the FBC sorting method in combination with innovative cultivation concepts addresses current limitations and challenges of continuous biopharmaceutical manufacturing and has great potential to further advance modern process intensification.